Members influence on one another during group decision-making in a South African bank . - Smith, Moegamad Riyaz (My University, 2016)
Today a significant proportion of decisions in the workplace are made by teams, groups, or committees. The purpose of this research was to quantify the mutual influences amongst members in a small decision making group and ascertain benefits and pitfalls in consensus decision making. This case study research focused on Barclays Africa Mortgage Change Council located in Johannesburg, South Africa. A critical review of the literature revealed when groups are required to reach consensus, individual members influence one another and this collective agreement results in decisions moving to more extreme positions. A model has been developed that determines how powerful each member of a group has been during interactions, and the influence of each group member on one another. Accordingly, this research analysed and evaluated the dynamics that occur before, during, and after discussions between decision makers to determine the influence members have on one another’s choice shifts. The study combines quantitative and qualitative research approaches to answer the research questions. To evaluate the dynamics that takes place during group interactions, five respondents were requested to rate ten attributes on two decision alternatives; before, during, and after group discussion. Qualitative data collected during separate semi-structured interviews with members after the group interaction, draws links to the quantitative modelling results established in the study. The research concludes that post-discussion preferences of members in a small decision making group can be modelled as a linear function of the members’ prediscussion preferences. Furthermore, buy-in and participation to implement group decisions improved when the members converged to reach consensus. This study assists organisations to identify the presence of “groupthink” and lessen flawed decision making in working group committees should consensus be valued over the best result.
MBA
Keywords: Communication in organizations,Group decision making ,Decision making -----South Africa